Progress in Episodic Memory Research - Ekrem Dere (Frontiers Research Topics, 2016)
Episodic memory refers to the ability to remember personal experiences in terms of what happened and where and when it happened. Humans are also able to remember the specific perceptions, emotions and thoughts they had during a particular experience. This highly sophisticated and unique memory system is extremely sensitive to cerebral aging, neurodegenerative and neuropsychiatric diseases. The field of episodic memory research is a continuously expanding and fascinating area that unites a broad spectrum of scientists who represent a variety of research disciplines including neurobiology, medicine, psychology and philosophy. Nevertheless, important questions still remain to be addressed. This research topic on the Progress in Episodic Memory Research covers past and current directions in research dedicated to the neurobiology, neuropathology, development, measurement and treatment of episodic memory.